A case report on efficacy of Abound™ for anti-EGFR antibody-associated skin disorder in metastatic colon cancer - Matsuhashi, Nobuhisa (BioMed Central, 2014)
BACKGROUND: Panitumumab is a full human epidermal growth factor receptor (EGFR) monoclonal antibody, an agent for metastatic colorectal cancer therapy. One of the most general adverse events of anti-EGFR monoclonal antibody therapy is skin disorder. At the present time, although prophylaxis of skin disorder is important for continuation of cancer therapy, there are no effective precautionary treatments. CASE PRESENTATION: A 73-year-old male with sigmoid colon cancer and synchronous lung metastasis was treated with panitumumab, an alone anti-EGFR monoclonal antibody as the third-line therapy. During the nine courses of the therapy, the response was stable disease (SD), but skin disorder gradually appeared obviously (CTCAE version 4.0: Grade 2). After 1 month of administration of Abound™, symptoms of the skin disorder improved (CTCAE version 4.0: Grade 1), thus the antibody therapy could be continued. CONCLUSION: We report that Abound™ was apparently effective in the treatment for anti-EGFR antibody-associated skin disorder. In the future, Abound™ could be expected as an agent for skin disorder as one of the side effects of colorectal cancer therapy.